EL PROGRAMA JOAQUÍN GALLEGOS LARA Y SU IMPACTO EN LA CALIDAD DE VIDA DE LAS PERSONAS CON DISCAPACIDAD SEVERA, MEDIDO DESDE LA DIMENSIÓN DEL BIENESTAR MATERIAL Y FÍSICO EN LA PARROQUIA SAN SEBASTIAN DEL CANTÓN LOJA, PERIODO 2018” - Ruiz Bermeo, Julissa Katherine (2019)
This research work entitled "The Joaquín Gallegos Lara Program and its impact on the quality of life of people with severe disabilities, measured from the dimension of material and physical well-being in the San Sebastián del Cantón Loja parish, period 2018", is carried out with the purpose of publicizing the impact of the Joaquín Gallegos Lara program on the quality of life of the beneficiaries. There are studies on the Joaquín Gallegos Lara program, but there are no results on the subject studied of the impact generated by the program on the quality of life of the beneficiaries, which is why it was decided to do an investigation to the beneficiary population in order to collect information if the program has managed to improve living conditions by assessing the material and physical dimension of the beneficiary. This research was carried out with the application of 75 surveys to the target population in order to obtain real information based, which allowed to fulfill the objectives set. In the same way, the development of the discussion and subsequent presentation of conclusions and recommendations of this work was carried out, it was carried out considering the legal regulations that govern the quality of life of people with disabilities.